Mitigating Financial Fraud and Cybercrime: A Systematic Literature Study - Ruslan, Mardiana (Penelitian dan Pengembangan Ilmu, 2024)
This research synthesizes and discusses various aspects of cyber security measures, fraud detection systems, response strategies, and future research directions. This research explores the limitations faced in cyber security research, including methodological constraints, data limitations, and challenges in generalizing results. Future research directions are proposed, focusing on the development of advanced technologies, the social and psychological impact of cybercrime, policy and legal implications, and cross-border cooperation. By addressing these limitations and pursuing future research directions, this research aims to improve the quality and relevance of cyber security research to effectively counter cyber threats.